Modified pulse-phase thermography algorithms for improved contrast-to-noise ratio from pulse-excited thermographic sequences. (December 2020) - Netzelmann, Udo; Müller, David
Abstract: Two modified algorithms for pulsed phase thermography were defined. The principle is to mask out parts of the thermal signal that only add noise but contain no significant information. A first algorithm uses a frequency dependent Gaussian window function. A second algorithm leads to a rectangular window function. The algorithms were tested on synthetic signals modeling a circular hidden defect in a plate and experimentally by flash excited thermography on a steel and a polymer sample. For both materials, a significant improvement of the contrast-to-noise ratio from the defects was obtained for higher analysis frequencies. Highlights: Improvement of defect contrast-to-noise ratio in pulse-phase thermography (for higher analysis frequencies) . Demonstration using an analytical defect model and corresponding experiments . Sensitive screening technique for pulsed excitation with unknown defect depth .